Poetic Devices and Cultural Representation in Lazarus' The New Colossus - Hendrayani, Dewa Ayu Febry; Laksminy, Luh Putu; Agung, I Gusti Ayu Mahatma (The Study Program of English Education of Palangka Raya University, 2025)
The New Colossus by Emma Lazarus is a well-known poem that expresses ideas of immigration, freedom, and national identity. This study aims to analyze the poem through two perspectives, namely poetic structure and cultural meaning. It focuses on how poetic devices such as metaphor, imagery, symbolism, alliteration and personification contribute to shaping the poem’s message. Using a qualitative method, the research applied Kemple's (2019) semiotic theory to interpret poetic devices as symbolic signs, while Hall's (2013) theory of representation was used to examine how the poem reflects and responds to changing social contexts. The analysis reveals that these poetic elements build a persuasive and emotional message that supports the poem’s theme of inclusivity and hope. It also shows that the meaning of the poem has shifted over time, especially in relation to modern immigration debates. This research highlights the poem’s dual role as a literary text and a cultural artefact. The findings suggest that poetic language can carry lasting social influence and that literature remains a relevant tool in understanding national identity.